PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPNEGERI 1 TALAMAU KABUPATEN PASAMAN BARAT - uspita Sari, Septian P; Zulfaneti, Zulfaneti; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACT The background of this research is the comprehension of mathematical concept of students grade VIII SMP Negeri 1 Talamau is low. The aim of this research are to know how students activities in learning process and is the comprehension of mathematical concept by apply Everyone Is a Teacher Here strategies is better than students comprehension of  mathematical concept by apply conventional learning in grade VIII SMP Negeri 1 Talamau Kabupaten Pasaman Barat. The type of the reseach is experiment. The sample study is class VIII.3 as experiment and VIII.1 as control class. The research instrument is a observation paper and test comprehension concept. Comprehension of the concept of test data analysis obtained an average of the concept of comprehension test are 68,33 for experiment class and 55,76  for control class. The analysis was done with help of software MINITAB obtainer P-value = 0,0444 is smaller that  = 0,05. Therefore, it can be concluded that the students who used active learning strategy type Everyone Is a Teacher Here better than students comprehension in mathematical concept in conventional learning.